35. INITIAL RESULTS OF THE TREATMENT OF DISTAL FEMORAL FRACTURE WITH THE LOCKING COMPRESSION PLATES FOR DISTAL FEMUR AT VIET DUC HOSPITAL 2019-2021 (Vietnam Journal of Community Medicine, 2023)
Objective: To evaluate the initial results of the treatment of distal femoral fracture with the locking compression plates for distal femur (LCP DF).Methods: A perspectively descriptive study was employed to carry out this research from January 2019 to June 2020.; 137 patients in VietDuc University hospital were operated on to be observed and evaluated for at least 12 months- follow up (1/2019-6/2021) by Schatzker and Lambert criteria.Results: Of the 137 patients, there were 85 males and 52 females. The average age was 58 (from 18 to 84). The average observation time was 23,3 months (minimally 12 months and maximally 29 months). The rate of bone union was 97.1%. Using the Schatzker and Lambert criteria to evaluate, we obtained good results with 76.64%, fair with 16.06%, average with 2,92% and poor with 4.38%.Conclusion: The treatment of distal femoral fractures initially achieved a high success rate. Locking plates united almost all kinds of distal femoral fractures, even in patients with osteoporosis.
Keywords: The locking compression plates for the distal femur (LCP DF).